Testing a Connectionist Model of Acquired Equivalence - Bru Garcia, Sara (2021)
Over the past decades, experimental research with animals has demonstrated that the generalisation between two stimuli is determined not only by their intrinsic properties, but by their associative history. This phenomenon is illustrated with the use of acquired equivalence tasks, which show that stimuli are treated as more similar when they come to elicit the same response as a result of conditioning. Different associative learning theories have been proposed to accommodate extant experimental findings. Mediated conditioning can explain simple forms of acquired equivalence (Honey & Hall, 1989), but is unable to accommodate findings from more complex configural acquired equivalence tasks, where stimuli are equally reinforced and nonreinforced. Pearce’s (1994) connectionist model and its extended version (Honey & Watt, 1998) can explain findings from revaluation configural acquired equivalence procedures, but cannot anticipate findings from other forms of configural acquired equivalence. Alternatively, Honey and colleagues (Honey, 2000; Honey et al., 2010) proposed a connectionist model that allows for similar inputs that share a common reinforcer to share hidden units. This model was able to accommodate a wide range of experimental findings that other models failed to explain.